ANALISIS PERKEMBANGAN KOGNITIF, SOSIAL DAN EMOSIONAL TERHADAP SISWA SEKOLAH DASAR YANG MENGALAMI ADHD - Puspa Pauziah; Ahmad Mulyadiprana, Anggit Merliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
At the elementary school level, students show very varied behaviors, such as pacing, being difficult to control, lacking concentration, etc. This is known as Attention Deficit Hyperactivity Disorder (ADHD). This study aims to analyze the cognitive, social and emotional development of students with ADHD. The research method is qualitative descriptive, with a phenomenological approach in which researchers collect data in the context of cognitive abilities and social emotional abilities of children with ADHD. The results of the study indicate that (1) the academic abilities experienced by student N are not good in reading and arithmetic, (2) social interaction is very good, student N likes to socialize with peers both in the school environment and in his home environment, (3) Student N is a person who is not easily offended, but when there is a desire that has not been fulfilled, student N's emotions are often uncontrolled and are expressed by going on hunger strike and staying silent in the room.